Optical and microphysical characterization of aerosol layers over South Africa by means of multi-wavelength depolarization and Raman lidar measurements - Giannakaki, Elina; van Zyl, Pieter G.; Müller, Detlef; Balis, Dimitris; Komppula, Mika (Atmospheric chemistry and physics, 2016)
Optical and microphysical properties of different aerosol types over South Africa measured with a multi-wavelength polarization Raman lidar are presented. This study could assist in bridging existing gaps relating to aerosol properties over South Africa, since limited long-term data of this type are available for this region. The observations were performed under the framework of the EUCAARI campaign in Elandsfontein. The multi-wavelength PollyXT Raman lidar system was used to determine vertical profiles of the aerosol optical properties, i.e. extinction and backscatter coefficients, Ångström exponents, lidar ratio and depolarization ratio. The mean microphysical aerosol properties, i.e. effective radius and single-scattering albedo, were retrieved with an advanced inversion algorithm. Clear differences were observed for the intensive optical properties of atmospheric layers of biomass burning and urban/industrial aerosols. Our results reveal a wide range of optical and microphysical parameters for biomass burning aerosols. This indicates probable mixing of biomass burning aerosols with desert dust particles, as well as the possible continuous influence of urban/industrial aerosol load in the region. The lidar ratio at 355 nm, the lidar ratio at 532 nm, the linear particle depolarization ratio at 355 nm and the extinction-related Ångström exponent from 355 to 532 nm were 52 ± 7 sr, 41 ± 13 sr, 0.9 ± 0.4 % and 2.3 ± 0.5, respectively, for urban/industrial aerosols, while these values were 92 ± 10 sr, 75 ± 14 sr, 3.2 ± 1.3 % and 1.7 ± 0.3, respectively, for biomass burning aerosol layers. Biomass burning particles are larger and slightly less absorbing compared to urban/industrial aerosols. The particle effective radius were found to be 0.10 ± 0.03, 0.17 ± 0.04 and 0.13 ± 0.03 µm for urban/industrial, biomass burning, and mixed aerosols, respectively, while the single-scattering albedo at 532 nm was 0.87 ± 0.06, 0.90 ± 0.06, and 0.88 ± 0.07 (at 532 nm), respectively, for these three types of aerosols. Our results were within the same range of previously reported values.